Defying barriers to fight tuberculosis in West Africa: a model of equitable partnerships within a research capacity-strengthening network in the subregion - Otchere, Isaac Darko; Edem, Victory Fabian; Togun, Toyin; Yeboah-Manu, Dorothy; Antonio, Martin; , the WANETAM-TB-Network (Frontiers in Public Health, 2025)
Tuberculosis (TB), caused by the Mycobacterium tuberculosis complex (MTBC), is the leading cause of death from a single infectious disease, despite being treatable. Global TB control efforts face significant challenges, including insufficient funding, ineffective vaccines, inadequate diagnostics, and complex treatments, particularly in resource-limited regions. West Africa has a unique TB epidemiology, characterized by medium- to high-prevalence rates and a greater diversity of the MTBC, which further compounds control efforts. In response to the global call to end TB by 2030, the West African Network of Excellence for TB, AIDS, and Malaria (WANETAM) has united scientists from 25 institutions across 12 West African countries to build research capacity and conduct translational research focused on TB. The multi-country program of WANETAM focuses on assisting the TB control programs of its member countries through the supply of essential laboratory equipment and the facilitation of laboratory accreditation/certification (with three regional laboratories already ISO accredited and others on track). The program also emphasizes gender-sensitive training, the retention of critical laboratory and research expertise, improvements in the diagnosis of TB (including pediatric and drug-resistant forms), and conducting studies on TB to better understand the molecular epidemiology of the MTBC in the sub-region, thereby generating the evidence to inform the policy. To date, WANETAM has trained 13 postdoctoral fellows, 753 laboratory technicians/technologists, and currently supports 7 female PhD students in the final year of their respective programs. By fostering collaboration among Francophone, Anglophone, and Lusophone West Africans, WANETAM is bridging cultural and language barriers to fight TB while also preparing West Africa for future pandemics.